Jupiter’s auroral-related stratospheric heating and chemistry II: Analysis of IRTF-TEXES spectra measured in December 2014 - Sinclair, J; Orton, G; Greathouse, T; Fletcher, L; Moses, J; Hue, V; Irwin, P (Elsevier, 2017)
We present a retrieval analysis of TEXES (Texas Echelon Cross Echelle Spectrograph (Lacy et al., 2002)) spectra of Jupiter's high latitudes obtained on NASA's Infrared Telescope Facility on December 10 and 11th 2014. The vertical temperature profile and vertical profiles of C 2 H 2 , C 2 H 4 and C 2 H 6 were retrieved at both high-northern and high-southern latitudes and results were compared in ‘quiescent’ regions and regions known to be affected by Jupiter's aurora in order to highlight how auroral processes modify the thermal structure and hydrocarbon chemistry of the stratosphere. In qualitative agreement with Sinclair et al. (2017a), we find temperatures in auroral regions to be elevated with respect to quiescent regions at two discrete pressures levels at approximately 1 mbar and 0.01 mbar. For example, in comparing retrieved temperatures at 70°N, 60°W (a representative quiescent region) and 70°N, 180°W (centred on the northern auroral oval), temperatures increase by 19.0 ± 4.2 K at 0.98 mbar, 20.8 ± 3.9 K at 0.01 mbar but only by 8.3 ± 4.9 K at the intermediate level of 0.1 mbar. We conclude that elevated temperatures at 0.01 mbar result from heating by joule resistance of the atmosphere and the energy imparted by electron and ion precipitation. However, temperatures at 1 mbar are considered to result either from heating by shortwave radiation of aurorally-produced haze particulates or precipitation of higher energy population of charged particles. Our former conclusion would be consistent with results of auroral-chemistry models, that predict the highest number densities of aurorally-produced haze particles at this pressure level (Wong et al., 2000, 2003). C 2 H 2 and C 2 H 4 exhibit enrichments but C 2 H 6 remains constant within uncertainty when comparing retrieved concentrations in the northern auroral region with quiescent longitudes in the same latitude band. At 1 mbar, C 2 H 2 increases from 278.4 ± 40.3 ppbv at 70°N, 60°W to 564.4 ± 72.0 ppbv at 70°N, 180°W and at 0.01 mbar, over the same longitude range at 70°N, C 2 H 4 increases from 0.669 ± 0.129 ppmv to 6.509 ± 0.811 ppmv. However, we note that non-LTE (local thermodynamic equilibrium) emission may affect the cores of the strongest C 2 H 2 and C 2 H 4 lines on the northern auroral region, which may be a possible source of error in our derived concentrations. We retrieved concentrations of C 2 H 6 at 1 mbar of 9.03 ± 0.98 ppmv at 70°N, 60°W and 7.66 ± 0.70 ppmv at 70°N, 180°W. Thus, C 2 H 6 's concentration appears constant (within uncertainty) as a function of longitude at 70°N.